THE ROLE OF THE UNITED NATIONS OF WOMEN IN ADDRESSING GENDER INEQUALITY IN EDUCATION IN ETHIOPIA THROUGH THE NATIONAL ACTION PLAN PROGRAM IN 2021-2023 - Eka Dwi Yanti; Sintia Catur Sutantri (Indonesian Journal of International Relations, 2026)
This study analyzes the role of UN Women in addressing gender inequality in Ethiopia’s education sector through the 2021–2023 National Action Plan (NAP). Using a qualitative descriptive method supported by document analysis and the theories of constructivism, international organizations, and gender equality. The study reviews NAP implementation through programs such as the Gender Transformative Norm Project, the Leadership for Results Programme, and the Education Equality for Climate Resilience Programme. The findings indicate improvements in women’s access to education, shifts in social norms, and stronger coordination between UN Women, the Ethiopian government, and local stakeholders. However, cultural resistance, limited resources, and disparities in educational quality continue to hinder progress. The study concludes that reducing gender inequality requires sustained long-term strategies and multi-sector collaboration to build an inclusive and gender-responsive education system that supports transformative and lasting change.